Evaluation of the reality of electronic banking services provided by banks operating in the city of Nasiriya from the users' point of view of these services - Muzeal, Wafaa Chetheer; Jasim, Layla Abed (Technium Business and Management, 2025)
This research aimed to identify the level and reality of electronic banking services provided by banks operating in the city of Nasiriya through a survey of the opinions of users of these services and thus to know the level of their satisfaction with the electronic banking services provided by the branches of banks operating in the city of Nasiriya, which are (Rafidain Bank, Rashid Bank and the Iraqi Trade Bank), as the study community consisted of customers of these banks and those dealing with electronic banking services. The descriptive analytical approach was used to evaluate the quality of electronic banking services provided by the banks surveyed by designing and distributing a questionnaire form to the target sample to measure the degree of quality of services, their type, and the difficulties facing electronic banking work, where the data extracted from the questionnaire form were studied and analyzed using the statistical program (SPSS). After analyzing this data, the research reached a set of results, the most important of which was the poor quality of electronic banking services provided by banks operating in the city of Nasiriya. Thus, they are below the required level compared to the electronic banking services provided by local and international banks and other competing banks. In light of these results, recommendations were made, the most important of which was for the banks in the research sample to work on raising the level of quality of services Electronic banking by developing and improving its websites and enabling customers to deal with them flexibly, as well as working to increase customers' confidence in electronic services and improve them in quantity and quality.